EFFECT OF ANNEALING ON MAGNETIC AND STRUCTURAL PROPERTIES OF THE NANOCRYSTALLINE Fe-Mn-Al ALLOYS - Kontan Tarigan; Darwin Sebayang (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2016)
In this work, the formations of Fe55Mn10Al35 nanocrystalline alloys were made by using mechanical alloying (MA) technique with the milling time of 24 hrs and then annealed at 300, 500, and 700oC. The sizes and the morphology of the particles were checked by using a Scanning Electron Microscope (SEM). The magnetic properties were characterized by using a Vibration Sample Magnetometer (VSM), and it give results both of the magnetic saturation (Ms) and Coercivity (Hc) are decreased respect to annealing temperatures. Last one; the structures were characterized by using an Extended X-ray Absorption Fine Structure (EXAFS) and X-Ray Diffraction (XRD). It give results that the structures were single phase at 24 hrs milled and 300oC annealed, then the structure to be changed at 500 and 700oC.